2010
DOI: 10.1002/cyto.a.20963
|View full text |Cite
|
Sign up to set email alerts
|

The snake venom peptide Bj‐PRO‐7a is a M1 muscarinic acetylcholine receptor agonist

Abstract: Proline-rich peptides from Bothrops jararaca venom (Bj-PRO) were characterized based on the capability to inhibit the somatic angiotensin-converting enzyme. The pharmacological action of these peptides resulted in the development of Captopril, one of the best examples of a target-driven drug discovery for treatment of hypertension. However, biochemical and biological properties of Bj-PROs were not completely elucidated yet, and many recent studies have suggested that their activity relies on angiotensinconvert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 50 publications
(60 reference statements)
0
20
0
Order By: Relevance
“…Thus, the hypothesis was raised that each Bj-PRO might act through distinct mechanism of action, probably involving different target proteins [9,23]. Recently, our group demonstrated that Bj-PRO-7a is a mAchR-M1 agonist [39], and Bj-PRO-10c action involves argininosuccinate synthase (ASS) activation, a key enzyme to provide substrate for NOS [13].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the hypothesis was raised that each Bj-PRO might act through distinct mechanism of action, probably involving different target proteins [9,23]. Recently, our group demonstrated that Bj-PRO-7a is a mAchR-M1 agonist [39], and Bj-PRO-10c action involves argininosuccinate synthase (ASS) activation, a key enzyme to provide substrate for NOS [13].…”
Section: Discussionmentioning
confidence: 99%
“…After loading with Fluo-3AM, the cells were incubated with extracellular buffer (140 mM NaCl, 3 mM KCl, 1 mM MgCl 2 , 2 mM CaCl 2 , 10 mM HEPES, 10 mM glucose at pH 7.4) [25]. Ca 2+ imaging was performed by using the Inverted Research Microscope ECLIPSE-TiS (Nikon, Melville, NY) equipped with a 14 bit high-resolution CCD camera CoolSNAP HQ2 (Photometrics, Tucson, AZ) and analyzed with NIS-Element software (Nikon) using image acquisition rates of two frames per second.…”
Section: Methodsmentioning
confidence: 99%
“…where K d is the dissociation constants of Fluo-3 (450 nM) or Fura-2 (224 nM), F is the variable fluorescence intensity, F max and F min are, respectively, the maximum and minimum fluorescence obtained in the presence of ionomycin (5 lM) or EGTA (20 mM) (16). F was substituted for R in the formula above when Fura-2 was used as fluorophore.…”
Section: Heterologous Expression Of Rtrpv1mentioning
confidence: 99%